The benefits of photobiomodulation in animal models of multiple sclerosis: a systematic review and meta-analysis - Ahmed, Zubair (Frontiers in Neurology, 2024)
Background Photobiomodulation (PBM), using red- or near-infrared light, has been used to treat tendinopathies, nerve injuries, osteoarthritis and wounds and evaluated in experimental allergic encephalomyelitis (EAE). To date, only a few studies have been performed in EAE but surprisingly, a few clinical studies in humans have already been performed, despite the paucity of preclinical evidence. Objective Therefore, this study systematically reviewed the usefulness of PBM in ameliorating the clinical signs of EAE, a commonly used animal model of multiple sclerosis, and determine if there is enough evidence to warrant human studies. Methods PubMed, EMBASE and Web of Science were searched in July 2024 for studies relating to PBM and EAE without any language restrictions. Since only three studies have been published, all studies were included in the systematic review and data related to clinical signs of EAE was pooled together to conduct a meta-analysis. Non-homogenous data was also reported and thematically synthesized. Results A meta-analysis of the pooled data from the three included studies demonstrated a significant reduction of the clinical severity of EAE, with a mean reduction of 1.44, 95% CI (−2.45, −0.42), p = 0.006. PBM also significantly reduced other parameters such as infiltration of mononuclear cells, CNS demyelination, apoptosis markers and pro-inflammatory cytokines. However, there was an overall high risk of bias in all of the studies. Conclusion The meta-analysis supports the use of PBM to ameliorate the symptoms of EAE, but the paucity of studies and the high risk of bias in the included studies warrants further preclinical investigation before conducting human studies.